The Effect of System Quality and Information Quality on User Satisfaction with Academic Information Systems - Hildawati Hildawati; Ilham Akbar Bunyamin; Paramita Andiani (Westscience Press, 2026)
This study aims to examine the effect of system quality and information quality on user satisfaction with Academic Information Systems (AIS) in Indonesia. A quantitative approach was employed using survey data collected from 150 respondents who actively use AIS in higher education institutions. Data were gathered through a structured questionnaire measured using a Likert scale. The analysis was conducted using IBM SPSS Statistics version 25, including validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results indicate that both system quality and information quality have a positive and significant effect on user satisfaction, both partially and simultaneously. System quality contributes through aspects such as ease of use, reliability, and responsiveness, while information quality is reflected in accuracy, relevance, and timeliness. Furthermore, information quality was found to have a stronger influence compared to system quality. The coefficient of determination (R²) shows that 48.3% of user satisfaction can be explained by the two independent variables. These findings highlight the importance of improving both system performance and the quality of information provided to enhance user satisfaction. This study provides practical implications for universities and system developers in optimizing academic information systems to better meet user needs and expectations.